Development and Validation of the Kidney Transplant Understanding Tool (K-TUT). Issue 3 (March 2017) - Rosaasen, Nicola; Taylor, Jeff; Blackburn, David; Mainra, Rahul; Shoker, Ahmed; Mansell, Holly
Abstract : Background: Several educational interventions have been designed to improve patient knowledge before and after kidney transplantation. However, evaluation of such interventions has been difficult because validated instruments to measure knowledge-based outcomes in this population have not been developed. Objective: To create a tool to measure patient knowledge of kidney transplantation and to evaluate its validity. Methods: The Kidney Transplant Understanding Tool (K-TUT) was created using a stepwise iterative process. Experts in the field and transplant recipients were consulted to establish content validity. The K-TUT consists of 9 true/false and 13 multiple-choice questions, and scores are based on the number correct answers [YES/NO format] of 69 items. The questionnaire was piloted in a study that also measured health literacy (via the Short Test of Functional Health Literacy) in transplant candidates, whereas the main survey was mailed to transplant recipients. Test-retest was performed, and completed surveys were analyzed for internal consistency, construct validity, floor and ceiling effects, and reproducibility. Results: Surveys were offered to 106 pretransplant patients and 235 in the posttransplant period, and response rates were 38.7% (41/106) and 63.4% (149/235), respectively. The mean corrected scores were 53.1 ± 8.5 (77%) and 56.2 ± 6.3 (81%), respectively. Test-retest was performed over 20% of both cohorts and percent agreement ranged between 70% and 100% in the pretransplant group and 66% and 100% in the posttransplant group. Cronbach α ranged from 0.794 to 0.875 in all cohorts indicating favorable internal consistency. Increased health literacy in the pretransplant group was significantly associated with increased knowledge ( r = 0.52; P < 0.001), suggestive of construct validity, and the absence of floor and ceiling effects was positive. The majority of transplant recipients (98/148, 67%) believed the questionnaire adequately assessed transplant knowledge, about a quarter (36/148, 24.3%) were "unsure, " and 85% (126/148) agreed that no questions should be removed. Conclusions: Although more study is warranted to further assess psychometric properties, the K-TUT appears to be a promising tool to measure transplant knowledge.